3D Finite Element Modeling and Modal Analysis of Planetary Gear System with Herringbone Gears - Lulu Qian; Peng Lou; Jin Feng; Jian Luo; Zhongtao Huang (Jixie chuandong)
A herringbone gear transmission system with star gear train is taken as the research object. In order to find the cause of system resonance， a modal-analyzing 3D finite element model is established to analyze the modal characteristics of herringbone gear transmission system of star gear train. Firstly， according to the experimental results of star gear train， the resonance caused by rotational frequency excitation and meshing frequency excitation is the main part of the vibration amplitude of the system. According to this phenomenon， a 3D finite element model is established based on the meshing stiffness matrix to analyze the modal characteristics of the system. The results show that the rotational frequency resonance mode and meshing frequency resonance mode obtained by simulation are uniquely corresponding to the experiment data， and the meshing frequency resonance mode is mainly represented by the fifth pitch diameter vibration mode of the inner gear and the torsional vibration mode of the coupled gear pair. This finite element model provides a valuable reference method for resonance prediction and resonance cause analysis of herringbone gear transmission system with star gear train.